2014
DOI: 10.3390/catal4030215
|View full text |Cite
|
Sign up to set email alerts
|

Enantiocomplementary Preparation of (S)- and (R)-Arylalkylcarbinols by Lipase-Catalysed Resolution and Mitsunobu Inversion: Impact of Lipase Amount

Abstract: A series of arylalkylcarbinol derivatives were deracemized through sequential combination of Candida antarctica lipase B (CAL-B) catalyzed resolution by hydrolysis and Mitsunobu stereoinversion. The (S)-acetates were obtained in 71%-99% ee and 76%-89% yields. An enantiocomplementarity was established for the hydrolysis and acylation reactions with CAL-B lipase. Thus, the (S) and (R) enantiomers of Indan-1-yl acetate, 1,2,3,4-tetrahydro-1-naphthalenol acetate and 1-(2-naphthyl) ethyl acetate were obtained in 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The same procedure was employed by Bouzemi and co‐workers in the deracemisation of a set of arylalkylcarbinol derivatives ( 26 ) employing the lipase B from Candida antarctica (CalB) and the Mitsunobu inversion reaction. CalB was able to catalyse the selective hydrolysis of the racemic starting material to the ( R )‐alcohols and ( S )‐acetates with high selectivity .…”
Section: Enzymatic Deracemisation Proceduresmentioning
confidence: 99%
“…The same procedure was employed by Bouzemi and co‐workers in the deracemisation of a set of arylalkylcarbinol derivatives ( 26 ) employing the lipase B from Candida antarctica (CalB) and the Mitsunobu inversion reaction. CalB was able to catalyse the selective hydrolysis of the racemic starting material to the ( R )‐alcohols and ( S )‐acetates with high selectivity .…”
Section: Enzymatic Deracemisation Proceduresmentioning
confidence: 99%
“…This prompted us to explore the reverse process, ie, lipase-catalysed deacetylation, which is also a well-recognized strategy to get enantio-pure compounds. 69 However, inconsistencies in conversions and enantio-selectivities were observed in the case of reactions in buffer. Subsequently, its enantioselective deacetylation was attempted with various lipases in phosphate buffer (pH 7.0) under ambient condition as per literature protocol.…”
Section: Enantioselective Deacetylation Route Tomentioning
confidence: 99%
“…Subsequently, its enantioselective deacetylation was attempted with various lipases in phosphate buffer (pH 7.0) under ambient condition as per literature protocol. 69 However, inconsistencies in conversions and enantio-selectivities were observed in the case of reactions in buffer. Literature reports also suggested that enzymatic hydrolysis in biphasic/aqueous conditions could pose problems due to difficulty in controlling pH, low solubility of the substrate, etc.…”
Section: Enantioselective Deacetylation Route Tomentioning
confidence: 99%
“…The complementary process was conducted using CAL-B on the catalyzed acylation of the rac -arylalkylcarbinols, producing the ( S )-alcohols and ( R )-acetates in high enantioselectivities (route b). Subsequently, these mixtures were submitted to a Mitsunobu reaction and provided only the ( R )-acetates (99% ee ( n = 1 or 2)), as seen in Scheme 45 b [ 69 ].…”
Section: Complementary Approaches: Hydrolysis and Esterificationmentioning
confidence: 99%
“… Complementary enzymatic kinetic resolution of rac -arylalkylcarbinyl acetates or rac -arylalkylcarbinols combined with Mitsunobu reaction on the preparation of ( S )- and ( R )-arylalkylcarbinyl acetates via hydrolysis ( a ) or acylation ( b ), respectively [ 69 ]. …”
Section: Complementary Approaches: Hydrolysis and Esterificationmentioning
confidence: 99%